Comparison of Tumor Necrosis Factor-α Level in Coronary Artery Disease and Coronary Slow Flow of Thrombolysis in Myocardial Infarction - Muhammad Diah; Rahmawati Rahmawati; Aznan Lelo; Zulfikri Muhktar; Dharma Lindarto; Ferry Sandra (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Tumor necrosis factor (TNF)-α, an important primary pro-inflammatory cytokine, has a crucial role in the pathogenesis of atherosclerosis. Since the pathophysiological mechanism of coronary slow flow (CSF) is not fully understood, we investigated the level of TNF-α in coronary artery disease (CAD), CSF and healthy subjects.METHODS: This study was conducted in cross-sectional design involving 16 CAD, 18 CSF and 18 healthy subjects. Coronary angiography was recorded at the left anterior oblique, cranial, right anterior oblique, caudal, and horizontal positions. The flow in coronary arteries of the subjects were assessed using Thrombolysis in the Myocardial Infarction (TIMI) frame count method. Peripheral blood-derived serum was collected and level of TNF-α was determined by using highly sensitive enzymelinked immunosorbent assay (ELISA).RESULTS: No significant difference in level of TNF-α in CAD, CSF and healthy subjects (2.72±2.64 pg/mL, 1.88±0.8 pg/mL, 1.64±0.35 pg/mL, respectively) (p=0.087). In addition, there was no correlation between the concentration of TNF-α and TIMI frame count (r<0.2, p>0.05).CONCLUSION: There was no significant difference of TNF-α level in CAD, CSF and healthy subjects. In addition, there was no correlation between the TNF-α level with TIMI frame count as well. Nevertheless, further clinical studies with more subjects are needed.KEYWORDS: TNF-alpha, coronary artery disease, coronary slow flow